Dinamika Spasial Industri Manufaktur di Jawa Barat, Tahun 1990 – 1999 - Zainal Arifin (Economic Journal of Emerging Markets, 2003)
This research aims to identify spatial concentration of large and medium manufac¬turing industries throughout 25 districts in West Java. It used secondary and establishment data of BPS (Indonesia’s Central Bureau Statistic) since 1990 until 199. The tools of analy¬sis are Geographic information system, logistic regression, regression using panel data and convergence analysis.The research showed that the industry growth in West Java was not distributed equally among districts. Several districts have a high industry concentration, meanwhile some have a low industry concentration. The manufacturing industries concentred in Bota¬bek (Bogor, Tangerang and Bekasi) and Bandung area. Factors that affect the growth are labor cost (salary), output, FDI, economics of scale (SE), dummy crisis (DKrisis) and dummy industry (DInd).Logistic regression analysis showed that, several variables were significantly ex¬plain that manufacturing industry are more concentrated on industrial regions. This result is consistent with regression analysis using panel data which shows that the manufacturing industrial growth was influenced by those above variables. Convergence analysis indicated that, West Java Province should growth at least 6.30% per year for its convergence growth. Keywords: spasial, convergence, manufacturing industries